Principles of Mixed-Initiative User Interfaces - Horvitz, Eric (Proceedings of CHI '99, ACM SIGCHI Conference on Human Factors in Computing Systems, Pittsburgh, PA, ACM Press., 1999)
Recent debate has centered on the relative promise of focusing user-interface research on developing new metaphors and tools that enhance users' abilities to directly manipulate objects versus directing effort toward developing interface agents that provide automation. In this paper, we review principles that show promise for allowing engineers to enhance human-computer interaction through an elegant coupling of automated services with direct manipulation. Key ideas will be highlighted in terms of the Lookout system for scheduling and meeting management.